Cohort trial reveals community impact of insecticide-treated nets on malariometric indices in urban Ghana - Klinkenberg, Eveline; Onwona-Agyeman, K.A.; McCall, P.J.; Wilson, M.D.; Bates, I.; Verhoeff, F.H.; Barnish, G.; Donnelly, M.J. (Oxford University Press, 2010)
The efficacy of insecticide-treated nets (ITNs) in prevention of malaria and anaemia has been shown in rural settings, but their impact in urban settings is unknown. We carried out an ITN intervention in two communities in urban Accra, Ghana, where local malaria transmission is known to occur. There was evidence for a mass or community effect, despite ITN use by fewer than 35% of households. Children living within 300 m of a household with an ITN had higher haemoglobin concentrations (0.5 g/dl higher, P = 0.011) and less anaemia (odds ratio 2.21, 95% CI 1.08-4.52, P = 0.031 at month 6), than children living more than 300 m away from a household with an ITN, although malaria parasitaemias were similar. With urban populations growing rapidly across Africa, this study shows that ITNs will be an effective tool to assist African countries to achieve their Millennium Development Goals in urban settings.